FUNCTIONAL OUTCOME OF MINIMALLY INVASIVE PERCUTANEOUS PLATE OSTEOSYNTHESIS AMONG PATIENTS WITH PROXIMAL TIBIA FRACTURES - SAEED, M; INAM, M; HAQ, SU (Biological and Clinical Sciences Research Journal, 2024)
Proximal tibia fractures are complex injuries that pose significant challenges in orthopaedic surgery. Minimally invasive percutaneous plate osteosynthesis (MIPPO) has been increasingly adopted as a treatment method due to its potential benefits in reducing soft tissue damage and promoting faster recovery. Objective: To assess the functional outcome of minimally invasive percutaneous plate osteosynthesis (MIPPO) among patients with proximal tibia fractures. Methods: A prospective cohort study was conducted in a tertiary care hospital over a period of two years, from January 2021 to December 2022. Thirty-five patients presenting with proximal tibia fractures were treated using the MIPPO technique. The Schatzker classification was used to categorize the fractures. Functional outcomes were assessed using the Knee Society Score (KSS) at six months postoperatively. Data were analyzed using descriptive statistics and chi-square tests to determine the significance of outcomes. Results: The most frequent type of fracture, according to Schatzker's classification, was type I, followed by type II and type III. An excellent outcome was observed in 21 patients (60%), good outcomes in 8 patients (22.9%), fair outcomes in 5 patients (14.3%), and poor outcomes in 1 patient (2.9%). Postoperative complications included infection in 2 patients (5.7%). Conclusion: Minimally invasive percutaneous plate osteosynthesis (MIPPO) is a safe and effective technique for managing proximal tibia fractures, yielding excellent functional outcomes in most patients.